Hot air and microwave combined drying of potato monitored by infrared thermography - Tomas Egea, Juan Ángel (2021)
Hot air drying (HAD) at temperatures below the spontaneous evaporation temperature could be combined with microwave (MW) radiation as a thermal energy source in order to reduce the drying time. A photon flux in the microwave range interacts with dipolar molecules (water) through orientation and induction, producing electrical energy storage and thermal energy accumulation and generating an increase in the internal energy of food. The different mechanisms involved in water transport could change when the microwave penetration depth exceeds the sample characteristic dimension of mass transport. The aim of this paper is to determine the effect of MW in the combined HAD-MW drying of raw potato in order to obtain the real driving forces and mechanisms involved in the water transport, with the purpose of optimizing the MW power used. For this purpose, combined drying was carried out on potato samples (0, 4 and 6 W/g). The sample surface temperature was monitored by infrared thermography, and the sample mass was measured continuously through a precision balance. In parallel with continuous drying, another drying treatment was performed at different times (20, 40, 60, 90, 120, 180, 420 min) and conditions (0, 4 and 6 W/g) to analyze the dielectric properties, mass, moisture, volume and water activity. The results show that it is possible to monitor combined drying by infrared thermography, and it can be concluded that the convection heating is mostly transformed into surface water evaporation, with negligible thermal conduction from the surface, and microwave radiation is mostly transformed into an increase in the potato’s internal energy.